Penanaman Literasi Budaya dan Kreativitas Melalui Pembelajaran Tari Tradisional Di SMP 1 Kabila Bone Sebagai Bentuk Objek Pemajuan Kebudayaan Daerah Kawasan Teluk Tomini - Nurlia Djafar; Novianty Djafri (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
Embedding cultural literacy in students requires effective learning with learning media where in learning, teachers can connect learning materials with culture, both national culture and local wisdom in students. Cultural literacy is the ability to understand and behave towards Indonesian culture as a national identity. Cultural literacy refers to a person's ability to understand, analyse and participate in culture effectively. This includes understanding the symbols, norms, values and cultural practices that exist in society. Dance as an art that shows the cultural heritage of a society and is a cultural expression that combines body movement and expression (Puspita Sari, 2022). Traditional dance is a representation of local culture. Learners can gain an understanding of the cultural principles contained in traditional dance movements and expressions by learning them they can feel and appreciate cultural diversity in a broader context. So the right approach is needed to improve cultural literacy in learners, to improve cultural literacy, one of which is by presenting traditional dance in schools.